A case study on a flexible floor plan design for South Korean apartments using two types of margins. Issue 2 (1st February 2022) - Yoon, Chaeshin; Kim, Marie; Park, Jinho; Lee, Jeayoung
Abstract : Purpose: The purposes of this study are to prove that the content of floor flexibility can be designed objectively with the use of margins, which are an architectural vocabulary visualizing the possibility of formal change, and to conduct a case study on how the existing typical floor plans of South Korean apartments change with the extension of flexibility: the usability of margins and the results. Design/methodology/approach: This study reviews two housing projects with different methods of flexible housing design: one is the flexibility to change the sizes of spaces and the other is the flexibility to change the topology of spaces. In this paper, the architectural term "area margin" is used for the former and "linear margin" for the latter. These were applied to the case of current apartments in South Korea to transform them into floor plans with the two types of flexibility and investigated whether the proposed floor plans satisfy the required efficacy structurally and functionally. Findings: This case study shows that margins can be used as architectural vocabularies representing flexible sizes of rooms and flexible boundaries with neighbors. The final form of the structural framework became homogeneous, even though it conserved its indigenous spatial characteristics of abundant natural sunlight and airflow. In addition, the transformed structural framework has higher rigidity than the original one, even though the transversal wall was cut off with a margin, as shown by the schematic representations in this paper. Research limitations/implications: The alternative plan, designed as a modification process, is not representative as a flexible floor plan. Rather, it is thought more important to make a range of variations rather than prototyping a model. This study starts from the premise that it is desirable for apartment house plans to share and encourage variations rather than aiming at typical sizes and shapes. Furthermore, this study exemplified the process to modify the existing typical floor plan into a flexible one using margins. Through this modification, it is thought that the typology of the South Korean apartment, which has succeeded in gaining social consensus for half a century, can be preserved while accommodating social changes in the future. Social implications: The control of future variations of floor plans will extend the socioeconomic and physical life of a building, enabling a reasonable reinvestment of resources. Originality/value: This paper deals with a design method applying distinct visual symbols to different contexts of flexibility and using those as architectural vocabularies.